IMPROVING STUDENTS’ VOCABULARY THROUGH TOTAL PHYSICAL RESPONSE - La Rasullah, La Rasullah (Journal of Basication (JOB) : Jurnal Pendidikan Dasar, 2017)
Abstract. This research is aimed to improve students’ vocabulary achievement under Total Physical Response (TPR) Method at class IX.1 students of SMP Negeri 1 Tongkuno. The subject of this research was the students of class IX.1 who enrolled in 201/2016 SMP Negeri 1 Tongkuno. Total subject was 20 students. The design of this research was classroom action research which applied four steps, namely planning, action, observation and reflection. This research was conducted in two cycles which applied three kinds of instrument, namely vocabulary test, observation sheet, and field note. The minimum target of this research was 70% of students got score ≥ 70. In teaching vocabulary under Total Physical Response (TPR) method the students sit in groups. In the first cycle the total of students who could get score 70 is 13 or 65% of 20 students with the mean score 67.60. In the second cycle indicates the fulfillment of the minimum target, that is85% or 17 students of 20 students at class IX.1 get score 70 with the mean score is 74.50. In brief, the result of this study verifies that Total Physical Response (TPR) can develop student’s vocabulary at class IX..1 of junior high school 1 Tongkuno.   Key words: Vocabulary, Total Physical Response (TPR)